Functional threshold power field test exceeds laboratory performance in junior road cyclists - Vinetti, G.; Rossi, H.; Bruseghini, P.; Corti, M.; Ferretti, G.; Piva, S.; Taboni, A.; Fagoni, N. (The Journal of Strength and Conditioning Research, 2023)
The functional threshold power (FTP) field test is appealing for junior cyclists, but it was never investigated in this age category, and even in adults, there are few data on FTP collected in field conditions. Nine male junior road cyclists (16.9 ± 0.8 years) performed laboratory determination of maximal aerobic power (MAP), 4-mM lactate threshold (P4mM), critical power (CP), and the curvature constant (W'), plus a field determination of FTP as 95% of the average power output during a 20-minute time trial in an uphill road. The level of significance was set at p < 0.05. Outdoor FTP (269 ± 34 W) was significantly higher than CP (236 ± 24 W) and P4mM (233 ± 23 W). The VO2_peak of the field FTP test (66.9 ± 4.4 ml·kg-1·min-1) was significantly higher than the VO2_peak assessed in the laboratory (62.7 ± 3.7 ml·kg-1·min-1). Functional threshold power was correlated, in descending order, with MAP (r = 0.95), P4mM (r = 0.94), outdoor and indoor VO2_peak (r = 0.93 and 0.93, respectively), CP (r = 0.84), and W' (r = 0.66). It follows that in junior road cyclists, the FTP field test was feasible and related primarily to aerobic endurance parameters and secondarily, but notably, to W'. However, the FTP field test significantly exceeded all laboratory performance tests. When translating laboratory results to outdoor uphill conditions, coaches and sport scientists should consider this discrepancy, which may be particularly enhanced in this cycling age category.